DOES ENGAGEMENT IN INDONESIA MATCH WA’D ACCOUNTING? - Muryani Arsal; Khalishah Ulfah; Ainun Arizah (Jurnal Magister Akuntansi Trisakti, 2023)
Marriage is the longest form of worship in human history and is carried out in social interactions that lead to high accountability to humans and Allah SWT. In most cases, before the marriage is carried out, it is preceded by a khitbah, or a proposal, better known as an engagement. Engagement is a wa'd that will be carried out in the future without violating the shari’a and does not require accounting records. This study aims to determine the engagement that occurred from the perspective of Islamic accounting. The data collection method was carried out by distributing an online questionnaire through Google Forms within 12 hours and studying the related documentation in research journals. The criteria for respondents who filled it out were only those who had done an engagement, and 27 respondents filled out the questionnaire. The data is analyzed with a qualitative-descriptive approach. The study results indicate that the engagement, which is a wa'd, has shifted into an aqad (contract) due to an agreement regarding the rights and obligations of the parties involved in the engagement. The engagement shows that there is a gift and transfer of assets that are part of the mahar (dowry), as well as the imposition of a fine if one of the parties cancels the engagement. This phenomenon had an impact on changes in asset ownership, which in accounting must be recorded, and the risk of future fines in the event of cancellation. The results of this study can be used to increase knowledge related to Islamic accounting through the social paradigm.